2006
DOI: 10.1002/jbm.a.30736
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of DNA release from composites of oligo(poly(ethylene glycol) fumarate) and cationized gelatin microspheres in vitro

Abstract: This research investigates the release of plasmid DNA from novel hydrogel composites of oligo(poly(ethylene glycol) fumarate) (OPF) and cationized gelatin microspheres (CGMS), as well as the swelling and degradation of these materials in vitro. The release of total DNA and of double-stranded DNA was measured fluorescently, and the swelling properties and polymer mass loss of the hydrogels were assessed. Further, the structural integrity of the released DNA was determined through electrophoresis. It was found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…Previous researchers have shown that drugs can be released from oligo-(polyethylene glycol) fumarate (OPF) hydrogel for a sustained time period [25,26]. The release profile can be tailored by changing the molecular weight of the polyethylene glycol, which changes the amount of crosslinking in the hydrogel [27].…”
Section: Introductionmentioning
confidence: 99%
“…Previous researchers have shown that drugs can be released from oligo-(polyethylene glycol) fumarate (OPF) hydrogel for a sustained time period [25,26]. The release profile can be tailored by changing the molecular weight of the polyethylene glycol, which changes the amount of crosslinking in the hydrogel [27].…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Potential applications of these hydrogels include bone tissue engineering, [24][25][26][27] scaffold material for marrow stromal cell attachment and differentiation, [28][29][30][31] cell encapsulation, 30,31 cartilage tissue engineering, 32 and the controlled release of various compounds. [33][34][35] Recent studies suggest applications in the nervous system using positively charged hydrogels. 36 These researchers demonstrate the capability of OPF hydrogels for sustaining growth of both primary nerve cells and neural support cells that are critical for regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…40,44 Novel approaches to PLGA microsphere incorporation into three-dimensional biodegradable scaffolds include fusion of protein loaded spheres into scaffolds using dichloromethane vapor. 45 While incorporation of PLGA microspheres into threedimensional OPF scaffolds has not yet been demonstrated, release of DNA 33,34,46 and growth factors 35 from gelatin microspheres within OPF hydrogels has been shown. To assess the feasibility of incorporating OPF hydrogel and PLGA microsphere technology, we sought to release dibutyryl cyclic adenosine monophosphate (dbcAMP) to the transected spinal cord.…”
Section: Introductionmentioning
confidence: 99%
“…Acidic GMPs, which are negatively charged at physiological pH, were loaded electrostatically with net positively charged TAPP/ pDNA polyplexes. These enzymatically degradable GMPs have been used previously to deliver both growth factors 9,10,12 and pDNA [13][14][15] in a sustained manner. The overall objective of this study was to evaluate the ability of composite scaffolds comprising pDNA complexed with a TAPP, GMPs, and a porous PPF scaffold to control the release of pDNA and induce bone formation in a critical-size rat cranial defect.…”
mentioning
confidence: 99%